Series Solution of the Multispecies Lotka-Volterra Equations by Means of the Homotopy Analysis Method - A. Sami Bataineh; M. S. M. Noorani; I. Hashim (Differential Equations and Nonlinear Mechanics)
The time evolution of the multispecies Lotka-Volterra system is investigated by the homotopy analysis method (HAM). The continuous solution for the nonlinear system is given, which provides a convenient and straightforward approach to calculate the dynamics of the system. The HAM continuous solution generated by polynomial base functions is of comparable accuracy to the purely numerical fourth-order Runge-Kutta method. The convergence theorem for the three-dimensional case is also given.